Use the four step process to find the derivative of f(x) where f'(x) = lim [f(x+h)-f(x)]/h (the lim is h to 0) :

f(x) = 1 / 4x-3

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Using the 4 step process you can find f'(x) below:

1) f(x+h) = 1/ (4(x+h)-3)  and f(x) = 1 / 4x-3

2) f(x+h) - f(x)= (4x - 3)/(4x + 4h - 3)(4x - 3) - (4x + 4h - 3)/(4x + 4h - 3)(4x - 3) = [ (4x-3)-(4x + 4h -3)] / (4x + 4h - 3)(4x - 3) = - 4h / 16x^2 + 16xh - 24x - 12h + 9

3) f(x+h) - f(x) / h = [- 4h /16x^2 + 16xh - 24x - 12h +9] / h = [- 4h /16x^2 + 16xh - 24x - 12h +9] * (1/h) =   (cancel h's)       - 4 /16x^2 + 16xh - 24x - 12h +9

4) as h --> 0 using step 3

f'(x) = lim f(x+h) - f(x) / h =

lim - 4 /16x^2 + 16xh - 24x - 12h +9     {as h --> 0}             = - 4 /16x^2 + 0 - 24x - 0 +9 = - 4 / 16x^2 - 24x + 9

So f'(x) = - 4 / (16x^2 - 24x + 9).

**** the quotient rule is much easier to use here, but as you can see, you should always get the same answer regardless of the method used***

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial